HCV-infected cells and differentiation increase monocyte immunoregulatory galectin-9 production. Issue 3 (16th October 2015) - Harwood, Noah M K; Golden-Mason, Lucy; Cheng, Linling; Rosen, Hugo R; Mengshol, John A
Abstract : HCV subject monocytes-derived macrophages increased gal-9, with the highest levels of non-classical monocytes. Abstract: The lectin galectin-9 may help establish and maintain chronic hepatitis C virus infection. Galectin-9 is elevated in the liver and sera of hepatitis C virus patients, induces apoptosis of hepatitis C virus-specific T cells, and increases inhibitory regulatory T cells. Kupffer cells stain strongly for galectin-9 protein in hepatitis C virus patients. In the current study, we determined stimuli that induce galectin-9 production by monocytes and macrophages in hepatitis C virus infection. With the use of real-time PCR and flow cytometry, we analyzed galectin-9 mRNA and protein from human monocytes cocultured with hepatitis C virus-infected cells or noninfectious hepatitis C virus subgenomic replicon cells. We focused on finding the stimuli for galectin-9 production. Additionally, we measured galectin-9 during monocyte-to-macrophage maturation. Finally, we examined galectin-9 in peripheral monocytes from hepatitis C virus patients using flow cytometry. Galectin-9 mRNA increased 8-fold when primary monocytes were exposed to hepatitis C virus–infected cells. Maximum induction required proximity or contact and did not require IFN-γ or hepatitis C virus virions. Coculture of monocytes with subgenomic replicon cells increased galectin-9 5-fold, and purified exosomes from infected cells stimulated galectin-9 production. Stimulation of monocyte TLR3, -7, and -8 increased galectin-9 production. Differentiation of monocytes to macrophages increased galectin-9, and nonclassic monocytes from hepatitis C virus patients had the highest levels of galectin-9. Hepatitis C virus-infected cells stimulated monocytes to produce galectin-9 in close proximity, possibly, in part, as a result of exosomes and endosomal TLRs. Differentiation of monocytes to macrophages increased galectin-9. Nonclassic monocytes from hepatitis C virus patients express the highest galectin-9 levels, suggesting they may contribute to elevated galectin-9 and adaptive immune inhibition in hepatitis C virus infection.